2003
DOI: 10.1046/j.1537-2995.2003.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of D– alloimmunization in AIDS patients receiving D‐mismatched RBCs

Abstract: Patients with AIDS may not form alloantibodies to the D antigen. This may be attributable to their immunodepressed state, particularly to the decrease in CD4+ T lymphocytes. Therefore, during blood shortages, transfusion of D+ blood to D- AIDS patients may be without any subsequent consequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 19 publications
2
29
0
1
Order By: Relevance
“…There are only a few studies evaluating the anti‐D alloimmunization rate in primarily nononcologic D– recipients. In one such study, 6 patients with various medical diagnoses, including 1 patient with adenocarcinoma of the rectum, received a mean of 3.3 D+ RBC units 12 . All were subsequently found to have produced anti‐D after a mean of 11.5 weeks of follow‐up 12 .…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies evaluating the anti‐D alloimmunization rate in primarily nononcologic D– recipients. In one such study, 6 patients with various medical diagnoses, including 1 patient with adenocarcinoma of the rectum, received a mean of 3.3 D+ RBC units 12 . All were subsequently found to have produced anti‐D after a mean of 11.5 weeks of follow‐up 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, disease- or therapy-associated immunosuppression results in decreased or even abolished tendency to develop RBCA [22,48,49]. Especially immunosuppressed solid organ transplant recipients subjected to immunosuppressive protocols to avoid or treat graft rejection have a markedly impaired alloimmune response with minimal RBCA rates [50,51,52].…”
Section: Clinical Factors Influencing Red Blood Cell Alloimmunizationmentioning
confidence: 99%
“…Only 16 of 78 (21%) D-negative patients of a mixed disease cohort showed anti-D after D-positive transfusions [12]. AIDS patients may not form anti-D after D-mismatched transfusions at all, possibly attributable to their immunosuppressed state with CD4-positive T-cell deficiency [48]. Likewise, also preterm infants known to have an immature immune system are unlikely to form RBCA [56].…”
Section: Clinical Factors Influencing Red Blood Cell Alloimmunizationmentioning
confidence: 99%
“…Studies deliberately exposing healthy D-negative volunteers to D-positive blood, to obtain IgG anti-D for immunoprophylaxis purposis, showed that appoximately eighty percent of D-negative individuals will produce serological detectable anti-D [68][69][70][71] . Studies on D-immunization after D-positive RBC transfusions in Dnegative patients reported comparable 72 or lower immunization rates [73][74][75][76][77][78][79] . In a number of these studies the low rate of D immunization is associated with a depressed immune system [73][74][75][76] .…”
Section: Immunogenicitymentioning
confidence: 99%